Claiming citizenship and nation - Pandit, Aishwarya, author.
1 online resource
Keywords: The book provides insight into the changing nature of Muslim politics and the ideas of citizenship in independent India. It studies the electoral mobilization of minority groups across North India, particularly in Uttar Pradesh where Muslims have been demographically dominant in various constituencies. The volume discusses themes such as the making and unmaking of the Congress heartland' and the threat of revival of Muslim communalism', alongside issues of representation, property, language politics, rehabilitation and citizenship, politics of Waqf, personal law and Hindu counter-mobilization. The author utilizes previously unused government and institutional files, private archives, interviews and oral resources to address questions central to Indian politics and society. An important intervention, this book will be useful for scholars and researchers of politics, Indian history, minority studies, law, political studies, nationalism, electoral politics, partition studies, political sociology, sociology and South Asian Studies.